Primary appendicular hemangiosarcoma and telangiectatic osteosarcoma in 70 dogs: A Veterinary Society of Surgical Oncology retrospective study. Issue 6 (26th July 2018) - Giuffrida, Michelle A.; Kamstock, Debra A.; Selmic, Laura E.; Pass, William; Szivek, Anna; Mison, Michael B.; Boston, Sarah E.; Fox, Leslie E.; Robat, Cecilia; Grimes, Janet A.; Maritato, Karl C.; Bacon, Nicholas J.
Abstract: Objective: To define and compare clinical characteristics of canine primary appendicular hemangiosarcoma (HSA) and telangiectatic osteosarcoma (tOSA), including signalment, presentation, response to treatment, and prognosis. Study design: Multi‐institutional retrospective study. Animals: Seventy dogs with primary appendicular HSA or tOSA. Methods: Patient data were obtained from institutions' medical records. Immunohistochemistry was applied to archived tissues to establish tumor type. Patient characteristics, treatment responses, and outcomes were described and compared by tumor type. Results: Forty‐one HSA and 29 tOSA were identified. Dogs with HSA were more likely than dogs with tOSA to be male and have hind limb tumors; 78% of HSA occurred in hind limbs, particularly the tibia. Dogs with tOSA weighed a median of 9.9 kg (95% CI 4.6‐15.3) more than dogs with HSA. Most dogs received antineoplastic treatment, predominantly amputation with or without adjuvant chemotherapy. Overall survival with local treatment and chemotherapy was 299 days (95% CI 123‐750) for HSA and 213 days (95% CI 77‐310) for tOSA. Younger age and more aggressive treatment were associated with longer survival in dogs with HSA but not tOSA. One‐year survival rates did not differ between dogs with HSA (28%) and those with tOSA (7%). Conclusion: Distinct clinical features were identified between HSA and tOSA in this population. Both tumors were aggressive, with a high incidence of pulmonary metastases. However, local treatment combined with chemotherapy led to an average survival 7 months for tOSA and 10 months for HSA. Clinical significance: HSA should be considered as a differential in dogs with aggressive lytic bone lesions, particularly medium‐sized dogs with tibial lesions. HSA has a unique clinical presentation but similar therapeutic response and outcome to OSA. Amputation and chemotherapy appear to prolong survival in some dogs with HSA and tOSA.